Απομόνωση, ταυτοποίηση και τεχνολογικός χαρακτηρισμός των οξυγαλακτικών βακτηρίων από γάλα της αίγας Μαχαιρά - Χατζησάββα, Αθηνά (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Machairas goat is a native breed of Cyprus, with unique characteristics. The Machaira breed has valuable genetic material to be preserved, while being part of the natural and cultural heritage. Up to now, only scare research studies have been undertaken on this Cypriot goat breed, in order to evaluate its microbiological profile. Therefore, this study aims to determine the microbial biodiversity, especially of the lactic acid bacteria (LAB) population of this milk, in order to develop the research and science of this breed. The raw goat milk microbiota is considered a good source of LAB and strains with good technological characteristics could be exploited as starters or adjunct cultures in food fermentations. Lactic acid bacteria play an important role in the fermentation processes, they have a long and safe history of application and consumption in fermented foods and beverages. This study dealt with the isolation, identification of lactic acid bacteria of Machaira's milk by molecular techniques and the technological characterisation of the bacteria. It was found that the microorganisms isolated belong to the genus Enterococcus and mainly E.faecium and E. lactis. Enterococcus is a diverse genus of lactic acid bacteria, which appear in large numbers in milk and dairy products, and also as a part of the natural microbiota. Strains with good acidifying and proteolytic activity (and a safe profile) amongst the isolated enterococci could be used as starting cultures in order to manufacture fermented products such as yoghurt, kefir, and others.
Keywords: Machairas goat; Microbial biodiversity; Lactic acid bacteria; Milk; Enterococcus; E.faecium; E. lactis; Αίγα; Φυλή Μαχαιρά; Μικροβιακή βιοποικιλότητα; Οξυγαλακτικά βακτήρια; Γάλα